Analysis of Effectiveness of QR Codes for the Storage and Rapid Access of Patient Medical Records - Yusfina Himayanti; B. Fitria Maharani; Musparlin Halid (Media of Health Research, 2026)
Background: The advancement of digital technology in healthcare continues to accelerate, offering new opportunities to improve efficiency, accuracy, and data security in medical record management. Aims: This study aims to analyze the effectiveness of using Quick Response (QR) Codes for storing and enabling rapid access to patient medical records in healthcare facilities. The integration of QR Codes is expected to streamline patient identification, reduce data retrieval time, and enhance data security through authentication and encryption features. Methods: A quasi-experimental design was applied, involving healthcare personnel as respondents to assess access speed and system reliability before and after QR Code implementation. Data were collected through access-time observations, user perception questionnaires, and security evaluations. Results: The findings indicate that QR Code utilization significantly improves data access speed and enhances system usability. Additionally, QR Code integration demonstrates potential to strengthen patient information security, although supplementary safeguards remain necessary. Conclusion: This study contributes to the development of more efficient, secure, and user-friendly electronic medical record systems, particularly for small to medium-scale healthcare providers. It also recommends adopting QR Code technology as part of Indonesia's ongoing digital health transformation.